Enhancing cultural inclusivity in primary schools: insights from Springer multicultural education data - Farid, Mujahidin; Murtadho, Nurul; Muslihati, Muslihati; Alfan, Muhammad; Minghat, Asnul Dahar; Othman, Nooraini (International Journal of Evaluation and Research in Education (IJERE), 2024)
Multicultural education is an essential approach for fostering inclusivity and promoting diversity within primary school settings. This systematic literature review aims to explore the issues employed in multicultural education within primary schools, utilizing a data source from Springer, a renowned academic publisher. This research applies the systematic review literature method with the preferred reporting items for systematic reviews and meta-analysis (PRISMA) protocol. The review examines scholarly articles published between 2018 and 2023 to identify trends, challenges, and best practices in the field. The findings of this review have implications for educators, policymakers, and practitioners in the field of education. The identified best practices, such as problem-based learning, social-emotional learning, and virtual field trips, can guide the development of curriculum frameworks, instructional approaches, and professional development programs that prioritize multicultural education in primary schools.